Physical activity, sedentary behaviour and risk of oesophago‐gastric cancer: A prospective cohort study within UK Biobank. Issue 8 (1st October 2018) - Kunzmann, Andrew T; Mallon, Kristian P; Hunter, Ruth F; Cardwell, Chris R; McMenamin, Úna C; Spence, Andrew D; Coleman, Helen G
Abstract : Background: Few observational studies have assessed the role of physical activity in oesophago‐gastric cancer risk. Objective: This prospective cohort study aimed to assess the association between physical activity and risk of oesophageal or gastric cancer. Methods: A cohort of 359, 033 adults aged 40–69 years were identified from the UK Biobank, which recruited participants between 2006 and 2010. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations between self‐reported levels of physical activity and screen‐based sedentary behaviour and risk of oesophageal and gastric cancer were calculated using Cox proportional hazards models. Results: During eight years of follow‐up (mean = 5.5), 294 oesophageal cancer and 217 gastric cancer cases were identified. Physical activity and screen‐based sedentary behaviour levels were not associated with overall oesophago‐gastric cancer risk. However, when compared with low levels, high physical activity levels were associated with a significantly reduced risk of gastric non‐cardia cancer (HR 0.58, 95% CI 0.37–0.95). Moderate physical activity levels were associated with a 38% reduced risk of oesophageal adenocarcinoma (HR 0.62, 95% CI 0.43–0.89), although no dose‐response association was apparent. Conclusion: Moderate, rather than high, physical activity levels were associated with the strongest reductions in oesophageal adenocarcinoma risk in this large UK prospective cohort.